Central Sets Theorem Near of an Idempotent in Wap-Compactification - Ali Pashapournia; Mohammad Akbari Tootkaboni; Davood Ebrahimi Bagha (Journal of Function Spaces)
A small part of real line which is very close to zero has rich combinatorial properties. The aim of this paper is to express and then prove some locally combinatorial concepts near a virtual idempotent by considering the wap-compactification of a semitopological semigroup S. The wap-compactification of a semitopological semigroup S, denoted by Sw, is the collection of all ultrafilters near η∈Sw that forms a compact subsemigroup of βSd, where Sd denotes S as discrete space.